Toppled Monuments and Black Lives Matter: Race, Gender, and Decolonization in the Public Space. An Interview with Charmaine A. Nelson - Abraham, Christiana (Atlantis, 2021)
This paper discusses the recent backlash against public monuments spurred by Black Lives Matter (BLM) protests in North America and elsewhere following the killing by police of George Floyd, an unarmed African-American man in the United States. Since this event, protestors have taken to the streets to bring attention to police brutality, systemic racism, and racial injustice faced by Black and Indigenous people and people of colour in the United States, Canada, Great Britain and some European countries. In many of these protests, outraged citizens have torn down, toppled, or defaced monuments of well-known historic figures associated with colonialism, slavery, racism, and imperialism. Protestors have been demanding the removal of statues and monuments that symbolize slavery, colonial power, and systemic and historical racism. What makes these monuments problematic and what drives these deliberate and spectacular acts of defiance against these omnipresent monuments? Featuring an interview with art historian Charmaine A. Nelson, this article explores the meanings of these forceful, decolonial articulations at this moment. The interview addresses some complex questions related to monumentalization and the public sphere, symbolism and racial in/justice. In so doing, it suggests that monuments of the future need to be reimagined and redefined contemporaneously with shifting social knowledge and generational change.